Systematic Optimization Study of Line-Start Synchronous Reluctance Motor Rotor for IE4 Efficiency - Huai-cong Liu (Machines)
With the strengthening of international motor efficiency regulations, the new line-start synchronous reluctance motor (LS-SynRM), which does not require magnets or control units, is being studied to improve the efficiency of motors in industrial applications. However, the LS-SynRM features a complex structure with numerous design parameters, requiring the consideration of various factors such as electromagnetic performance, mechanical strength, starting capability, and ease of manufacturing. Additionally, starting capability analysis consumes a large amount of transient calculation time. The prototype stage typically comes after all simulation resources have been exhausted. The aim of this paper is to optimize the LS-SynRM by splitting the starting analysis and steady-state analysis, using a metamodel-based optimization method to quickly identify rotors of varying complexity (magnetic barriers and ribs) that meet steady-state efficiency and mechanical strength requirements. Finally, the rotor slot structure for starting is optimized within the magnetic barrier space. This approach significantly reduces the total optimization time from several weeks to just a few days. The final model obtained through the design process is analyzed using finite element analysis (FEA), and the results indicate that the target performance is achieved. To verify the FEA results, the final model is manufactured, and experiments are conducted.